2011
DOI: 10.1002/jnr.22555
|View full text |Cite
|
Sign up to set email alerts
|

Delayed administration of dapsone protects from tissue damage and improves recovery after spinal cord injury

Abstract: After spinal cord injury (SCI), a complex cascade of pathophysiological processes increases the primary damage. The inflammatory response plays a key role in this pathology. Recent evidence suggests that myeloperoxidase (MPO), an enzyme produced and released by neutrophils, is of special importance in spreading tissue damage. Dapsone (4,4'-diaminodiphenylsulfone) is an irreversible inhibitor of MPO. Recently, we demonstrated, in a model of brain ischemia/reperfusion, that dapsone has antioxidant, antiinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
(44 reference statements)
2
24
0
4
Order By: Relevance
“…Likewise, dapsone enhanced the functional recovery and increased the amount of tissue preserved in animals with permanent brain ischemia [12]. Our group has also demonstrated its neuroprotective effect with better functional recovery in a rat SCI model [13]. Finally, we have also reported the anti-oxidant, neuroprotective and anticonvulsant effects of dapsone in a model of excitotoxic damage by kainic acid in rats [14].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Likewise, dapsone enhanced the functional recovery and increased the amount of tissue preserved in animals with permanent brain ischemia [12]. Our group has also demonstrated its neuroprotective effect with better functional recovery in a rat SCI model [13]. Finally, we have also reported the anti-oxidant, neuroprotective and anticonvulsant effects of dapsone in a model of excitotoxic damage by kainic acid in rats [14].…”
Section: Introductionmentioning
confidence: 78%
“…It has also been demonstrated that dapsone suppresses intra-and extracellular production of superoxide in isolated human neutrophils [32]. The antioxidant effect of dapsone has been also shown indirectly by measuring lipid peroxidation both after ischemia with reperfusion, and SCI [10,13].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 The secondary damage is characterized by ischemia, inflammation, glutamate excitotoxicity, oxidative stress and production of free radicals. 5 Soluble CD95L (sCD95L) is activated by cleavage of mCD95L by the serine matrix metalloproteinases MMP-7 and MMP-3. 6 sCD95L cannot trigger apoptosis, but induces the production of proinflammatory chemokine in neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…MPO activity was measured as previously described [35]. Briefly, tissues were homogenized in ice-cold phosphate buffer (PB).…”
Section: Methodsmentioning
confidence: 99%